Change of Currency value and its impact on debts repayment (Salam International Academic Journal, 2023)
In the contemporary era, the fluctuation in the value of money is a significant concern that directly impacts individuals and communities. Islamic Sharia scholars have recognized this as a juridical emerging issue and have extensively addressed it. They assert that the nature of money, its characteristics, printing, and the quantity of issuance are matters within the purview of government authority to safeguard the currency's value.The primary objective of this article is to elucidate the Sharia ruling regarding the repayment of debts in cases of changes in the value of money. If the debt is denominated in gold, dinars, silver, or dirhams, jurists unanimously contend that changes in value are not considered, and the debtor is obligated to repay the same amount originally owed. Similarly, when the debt is in the form of metal money, it is generally treated like gold and silver, with changes in value not being recognized. However, Imam Abu Yusuf (RA) holds a distinct view. He posits that in both scenarios, whether there's an increase or decrease in the value of metal money, the debtor should repay the debt based on the prevailing price on the day the loan was initiated. This viewpoint aligns with the Hanafi school of thought.Contemporary scholars offer two primary perspectives concerning the repayment of debts denominated in modern customary paper money, contingent upon specific circumstances:1.      Usual Situation: When a country's currency remains stable without significant inflation or drastic value fluctuations, minor variations are not considered in debt repayment. This is because prices of goods fluctuate naturally over time, but these changes are not factored into loan repayment calculations.2.      Exceptional and Special Situation: In cases where a country's currency rapidly loses value due to unusual circumstances, the term "ghabnfahish" or deceit comes into play. In such situations, if a debt is repaid in the same quantity as originally owed, the creditor may not receive their full entitlement. To address this, knowledgeable scholars should calculate the difference and ensure compensation for the loss.Regarding currency demonetization by a government, there are two scenarios:1.      When a government demonetizes its old currency and replaces it with a new one without a significant change in value. In such cases, individuals typically have a specified period to exchange their old currency for the new one. Money in bank accounts is updated automatically, and creditors receive their due in the new currency, rendering the demand for the old currency unnecessary.2.      When a government demonetizes old currency and introduces new currency with a significant difference in value. For instance, when the current Afghani replaced the previous currency during Professor Rabani's government, and the new currency held a higher.